Amygdala neural ensemble mediates mouse social investigation behaviors. Issue 1 (30th August 2022) - Wei, Ji-an; Han, Qing; Luo, Zhihua; Liu, Linglin; Cui, Jing; Tan, Jiahui; Chow, Billy K C; So, Kwok-Fai; Zhang, Li
ABSTRACT: Innate social investigation behaviors are critical for animal survival and are regulated by both neural circuits and neuroendocrine factors. Our understanding of how neuropeptides regulate social interest, however, is incomplete at the current stage. In this study, we identified the expression of secretin (SCT) in a subpopulation of excitatory neurons in the basolateral amygdala. With distinct molecular and physiological features, BLA SCT+ cells projected to the medial prefrontal cortex and were necessary and sufficient for promoting social investigation behaviors, whilst other basolateral amygdala neurons were anxiogenic and antagonized social behaviors. Moreover, the exogenous application of secretin effectively promoted social interest in both healthy and autism spectrum disorder model mice. These results collectively demonstrate a previously unrecognized group of amygdala neurons for mediating social behaviors and suggest promising strategies for social deficits.